The global regulator VeA modulates ATP sulfurylase to mediate adenosine synthesis resulting in inhibitory activity of endophytic Fusarium solani against A549 cells - Jiang, Yuling; Cai, Lu; Xiao, Qing; Liu, Guihua; Liu, Rongfei; Zhao, Yan; He, Zhangjiang; Kang, Jichuan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Adenosine is an endogenous nucleoside that promotes apoptosis in cancer cells. Overexpression of the global regulator VeA gene (FsveA) in Fusarium solani resulted in the accumulation of multiple secondary metabolites, including adenosine. In this study, we utilised transcriptome and metabolome data to speculate on the key genes that impact adenosine synthesis in fungi. The c35754.graph_c1 gene encodes an ATP sulfurylase (Fsmet3) that was significantly up-regulated in F. solani mutant overexpressing VeA (FsveAOEV14). The qRT-PCR results were consistent with the transcriptome data, indicating that Fsmet3 was regulated by FsveA. Overexpression of Fsmet3 (Fsmet3OE) resulted in a significant increase in adenosine content and the inhibitory activity of the fungi against the human non-small cell lung cancer A549 cells. Moreover, analysis of Fsmet3OE metabolome showed that Fsmet3 not only up-regulated adenosine, but also significantly increased the accumulation of anti-tumor active substances such as resorufin and 13S-hydroxydodecanoic acid. Overall, our findings demonstrated that FsveA regulates Fsmet3 to mediate adenosine synthesis, resulting in potent inhibitory effects against A549 cells by endophytic F. solani.